Can Green Practices Reduce Tax Avoidance? Linking Environmental Performance and Sustainability - Dian Sulistyorini Wulandari; Vista Yulianti; Wisnu Setyawan (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study investigates the relationship between green practices and corporate tax avoidance, focusing on green accounting, environmental performance, and corporate social responsibility (CSR) among 19 Indonesian publicly listed companies from 2021 to 2024. The research aims to examine whether environmentally responsible strategies influence firms’ tax behavior and how sustainability practices mediate this relationship. A quantitative approach was employed, collecting data from corporate financial statements, ESG reports, and sustainability disclosures. The analysis included descriptive statistics, correlation tests, and pooled ordinary least squares regression to explore the effects of green accounting, environmental performance, and CSR on the effective tax rate (ETR) as a proxy for tax avoidance. Results indicate that green accounting is positively associated with higher ETR, suggesting reduced tax avoidance, while CSR negatively impacts ETR, implying that sustainability initiatives can be strategically used to mask aggressive tax planning. Environmental performance alone does not significantly affect tax behavior. These findings highlight the importance of transparency through green accounting to promote ethical tax practices, while cautioning that CSR may serve as a reputational tool rather than a mechanism for reducing tax avoidance. The study contributes to theoretical understanding in sustainability and corporate governance and offers practical insights for policymakers and corporate managers to align environmental and fiscal responsibilities.